2022
DOI: 10.1016/j.dcn.2021.101056
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and topographical changes in theta power between middle childhood and adolescence during sentence comprehension

Abstract: Time frequency analysis of the EEG is increasingly used to study the neural oscillations supporting language comprehension. Although this method holds promise for developmental research, most existing work focuses on adults. Theta power (4–8 Hz) in particular often corresponds to semantic processing of words in isolation and in ongoing text. Here we investigated how the timing and topography of theta engagement to individual words during written sentence processing changes between childhood and adolescence (8–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…In line with similar work investigating the developmental trajectory of neural oscillations during written sentence comprehension ( Maguire et al, 2022 ) and word reading ( Spironelli and Angrilli, 2010 ) tasks, we found age-related changes in task-relevant theta band activity near the onset of pseudowords, predominantly over left-hemisphere regions. Changes in theta band activity over left-hemisphere regions aligns with the majority of adult studies in the language processing literature (e.g., Hald et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with similar work investigating the developmental trajectory of neural oscillations during written sentence comprehension ( Maguire et al, 2022 ) and word reading ( Spironelli and Angrilli, 2010 ) tasks, we found age-related changes in task-relevant theta band activity near the onset of pseudowords, predominantly over left-hemisphere regions. Changes in theta band activity over left-hemisphere regions aligns with the majority of adult studies in the language processing literature (e.g., Hald et al, 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…Past studies of sentence processing indicate that frequency dynamics in the theta (4–7 Hz) and beta (14–20 Hz) frequency ranges are centrally involved in sentence comprehension and lexical processing ( Maguire et al, 2022 , Lam et al, 2016 ; Bastiaansen et al, 2005 ; 2006; Schneider et al, 2016 , Schneider et al, 2018 ; Lewis and Bastiaansen, 2015 ). Specifically, theta is hypothesized to reflect semantic retrieval processes during single-word and sentence comprehension and is often positively associated with retrieval demands from long-term memory.…”
Section: Introductionmentioning
confidence: 99%
“…In children, typical reading abilities (word-level and comprehension) and receptive vocabulary were confirmed with English versions of the Test of Word Reading Efficiency-Second Edition (Torgensen et al, 2012), Gray Oral Reading Tests (Wiederholt & Bryant, 2012), and Peabody Picture Vocabulary Test-4 (PPVT-4; Dunn & Dunn, 2007), respectively. Because data for the current study were collected from a larger study on the links between socioeconomic status and brain and language development (Maguire et al, 2022;Ralph et al, 2020;Schneider et al, 2021Schneider et al, , 2023, a portion of this study included an electroencephalogram task, not presented here, which required that all participants were right-handed children with no history of significant neurological issues (traumatic brain injury, cerebrovascular accident, seizure disorders, history of high fevers, tumors, or learning disabilities) or medications other than over-the-counter analgesics, as per parent and self-report. This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Efficiently retrieving and integrating word meanings into a coherent sentence is a complex process in which children perform quickly and seemingly effortlessly. Nevertheless, children continue to enhance their language skills through middle childhood and adolescence [1][2][3][4][5][6][7][8]. As children progress through their school years, their ability to retrieve semantic information becomes faster and more efficient [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, there remains a dearth of research investigating the neural oscillatory activity that supports sentence processing in children. A handful of studies have shown developmental differences in theta response during sentence processing in children [2,19]; however, further research is needed to fully understand the complex neural mechanisms that children use as they retrieve words and integrate them into coherent sentences.…”
Section: Introductionmentioning
confidence: 99%